Pobreza, niñez y diferenciación social - Montesinos, María Paula (2003)
The existence of the children that live in contexts of urban poverty an cultural diversity is crossed by several dimensions. In this article we explore the dimensions that became present in the schools they attend, located in the south area of the city of Buenos Aires. The different representations and practices conceming to this "childhood", contribute to the production of institutional spaces of inclusion/exclusion and, by the other hand, to the conformation of the social, schooling and urban itineraries that these children actually go through. To examine these complex crossings is the purpose of this work. The empiric material that supports this study is based on a wide group of interviews conducted with directors of primary schools of the mentioned area.